Analysis Of Food And Beverage Service To Increase Guest Satisfaction During The Covid-19 Pancemic At Renaissance Bali Uluwatu Resort & Spa - Ayu Oka Karismayani, I Dewa; Rajin Aryana, I Nyoman (Politeknik Sahid, 2022)
Purpose: The purpose of this research is to know the quality of food and beverage service to guest satisfaction at Renaissance Bali Uluwatu Resort & Spa during the COVID-19 pandemic and to know which indicators need to be improved and maintained in the quality of service performed by food and beverage staff. Methods: The data collection methods are observations, questionnaires, and interviews. The samples used in this study were 80 respondents. Data obtained through disseminating questionnaires has been tested for validity and reliability. The analysis techniques used in this study are servqual (service quality) and IPA (importance-performance analysis). Results and discussion: The effects of importance-performance analysis showed a gap in positive servqual scores more than negative servqual scores; it showed that the quality of food and beverage service staff during the COVID-19 pandemic at Renaissance Bali Uluwatu Resort & Spa as a whole has demonstrated good service. Indicators that need to be improved in the quality of service can be seen in the X2 attributes related to the preparation and arrangement of tables in the restaurant by the distance of at least 2 meters between guest tables and X6 attributes associated with the ability of staff in meeting health protocols during the covid-19 pandemic. Implication: Indicators that need to maintain the quality of service There are seven indicators, including X1, X7, X12, Y1, Y2, Y4, and Y7.